Savings of Population in Lithuania: Models of Women’s and Men’s Behaviour - Rakauskienė, Ona Gražina; Bikas, Egidijus (Ekonomika, 2007)
Savings of residents are one of the most important economic notions performing exceptionally significantly at both macro and micro levels, first of all in solving the problems of trade and service development, economic structural changes and social problems. Obviously, there is not enough attention to the problem of saving which is generated by the real practice in our country. Therefore, this article is one of the first attempts to bring forward the problem and to suggest some aspects of formation of residents’ savings. Firstly, it is attempted to define personal savings, to detect the mechanism of their formation (factors, motives, financial behaviour of residents). Then, the aim is to detect differences between women’s and men’s saving behaviour and to evaluate priorities of their financial investment. The process of saving is perceived by authors as follows: it is a system where three basic levels are distinguished: factors influencing the process of saving (at macro and micro levels), motives and aims of savings, savings formed, and the forms of their use. In the discussed period, four core factors were significant for the residents’ savings: the third wave economic migrations; the descending number of habitants and a more intense public obsolescence, shadow economy (or unofficial economy that is not recorded) degrees in the state, the high level of poverty and a high social-economic differentiation. The survey indicates the main tendency: the monthly income of Lithuanian women almost in all age groups is lower than men’s monthly income. More than 53.5% of women and more than 55.6% of men schedule their savings. Younger women tend to schedule more than men. The analysis detected core differences in men’ and women’s saving behaviour and highlighted their saving motives. Women save in order to increase consumption, men save in order to increase their income, wealth and to create investment; women schedule savings at a younger age, while men do it at an older age; women are more prone to save monetary means for specific saving purposes, men do not specify their aims; women are more attentive to specific saving aims than men. Quite a number of young people in Lithuania do not save (do not care of their future). In summary, the means used by Lithuanian men and women for saving are very conservative, especially in who mostly use bank deposits and other less risky and less profitable instruments. Men risk more and make saving investments into more risky and more profitable instruments. Younger individuals are better familiarized with “new” financial instruments than their parents.